2020
DOI: 10.1088/1742-6596/1439/1/012044
|View full text |Cite
|
Sign up to set email alerts
|

Specific absorption rate of assembly of magnetic nanoparticles with uniaxial anisotropy

Abstract: Specific absorption rate of superparamagnetic nanoparticles with uniaxial magnetic anisotropy has been calculated both for dilute assembly and for assembly of nanoparticle clusters with various filling factors using numerical simulation. The optimal particle diameters at which the specific absorption rate of assembly reaches a maximum have been obtained depending on the value of the uniaxial anisotropy constant. The optimal particle diameters are found to shift to smaller values with an increase in the anisotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Note that earlier [30] a similar behavior of SAR was revealed for randomly oriented assemblies of spherical iron oxide nanoparticles with saturation magnetization Ms = 350 emu/cm 3 depending on the value of the effective uniaxial magnetic anisotropy constant in the range Ku = 10 4 -510 5 erg/cm 3 .…”
Section: Sar Of Dilute Randomly Oriented Assemblysupporting
confidence: 73%
See 2 more Smart Citations
“…Note that earlier [30] a similar behavior of SAR was revealed for randomly oriented assemblies of spherical iron oxide nanoparticles with saturation magnetization Ms = 350 emu/cm 3 depending on the value of the effective uniaxial magnetic anisotropy constant in the range Ku = 10 4 -510 5 erg/cm 3 .…”
Section: Sar Of Dilute Randomly Oriented Assemblysupporting
confidence: 73%
“…In theoretical studies [18][19][20][21][22][23] spherical magnetic nanoparticles are usually considered. A theoretical study of assemblies of spherical nanoparticles with 10 uniaxial [18][19][20][21]23,30] and cubic [25] magnetic anisotropy showed the existence of an interval of optimal nanoparticle diameters where the SAR of the assembly reaches maximum at a given frequency and amplitude of ac magnetic field. In this work, using numerical simulation, similar results were obtained for spheroidal magnetite nanoparticles in the range of aspect ratios a/b = 1.0 -3.0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, , where is the frequency dependent hysteresis loop area for an alternating magnetic field in terms of the nanoparticle magnetization M , and the external magnetic field . The value of A strongly depends on the size of the magnetic nanoparticles and there is always an optimal size of magnetic nanoparticles for which the heating rate is the highest [ 71 , 72 ]. This applies also to iron-based colloids in alkaline conditions [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of magnetic nanoparticles with increased value of magnetic anisotropy constant was assumed [ 28 29 ] to be promising in magnetic hyperthermia. However, numerical simulations [ 30 ] showed that for spherical nanoparticles an increase of the uniaxial anisotropy constant leads to a decrease in SAR and a shift of the optimal particle diameters to smaller dimensions.…”
Section: Introductionmentioning
confidence: 99%